2007
DOI: 10.1056/nejmoa063971
|View full text |Cite
|
Sign up to set email alerts
|

Clomiphene, Metformin, or Both for Infertility in the Polycystic Ovary Syndrome

Abstract: Clomiphene is superior to metformin in achieving live birth in infertile women with the polycystic ovary syndrome, although multiple birth is a complication. (ClinicalTrials.gov number, NCT00068861 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
486
7
25

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 897 publications
(548 citation statements)
references
References 33 publications
18
486
7
25
Order By: Relevance
“…This result contrasts with data observed in hyperandrogenic patients without T1D, who experience increases in ovulation, menstrual cyclicity and pregnancy rates upon treatment with metformin [32,33,34,35]. We hypothesize that ovulatory function in adolescents with T1D does not change upon metformin treatment because the ovulatory function was similar to healthy control girls at a basal level.…”
Section: Discussioncontrasting
confidence: 55%
“…This result contrasts with data observed in hyperandrogenic patients without T1D, who experience increases in ovulation, menstrual cyclicity and pregnancy rates upon treatment with metformin [32,33,34,35]. We hypothesize that ovulatory function in adolescents with T1D does not change upon metformin treatment because the ovulatory function was similar to healthy control girls at a basal level.…”
Section: Discussioncontrasting
confidence: 55%
“…From the remaining 106 articles, 60 were excluded on the basis of the abstract. For the remaining 46, we obtained full manuscripts and following scrutiny of these, we identified 32 potentially relevant studies; 6 publications were duplicated [19,20,21,22,23,24]. From these 32, another 4 were excluded because they included women with PCOS who were CC resistant.…”
Section: Resultsmentioning
confidence: 99%
“…Another randomized controlled trial involving 626 infertile women with PCOS demonstrated the rates of miscarriage in the first trimester did not differ significantly among the group that received metformin only, the group that received clomiphene only, and the combination therapy group. The live-birth rate of the metformin group was however lower than that of the clomiphene citrate and combination groups (7.2, 22.5, and 26.8%, respectively) [20]. Two meta-analyses conducted by Palomba et al [21,22] to evaluate the effect of ovulatory rate of metformin only and metformin + clomiphene citrate found out that neither metformin nor metformin + clomiphene citrate could reduce the rate of miscarriage.…”
Section: Discussionmentioning
confidence: 99%